2016
DOI: 10.1186/s13104-016-2178-0
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent hyperthyroidism and papillary thyroid cancer: a fortuitous and ambiguous case report from a resource-poor setting

Abstract: BackgroundConcurrent thyroid cancer (TC) and hyperthyroidism (HT) is rare though increasingly being reported. HT due to TC is much rarer and more challenging especially in Africa where TC and HT have significant case fatality rates.Case presentationWe present a 37-year-old Cameroonian female who had been on irregular regimens of propranolol and digoxin as treatment for worsening palpitations for 12 months. She came to our district hospital for her propranolol medication refill. We fortuitously identified featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 10 publications
1
11
0
Order By: Relevance
“…The literature search identified 43 cases of primary hyperfunctioning thyroid carcinoma between 1998 and 2017 (Table I) that fulfilled the inclusion criteria (3,528); the full-text versions of the majority of articles published before 1998 were unavailable. The mean age of patients was 50.1±19.0 years (range, 11–79 years) and the female:male ratio was 2.31 (30:13).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature search identified 43 cases of primary hyperfunctioning thyroid carcinoma between 1998 and 2017 (Table I) that fulfilled the inclusion criteria (3,528); the full-text versions of the majority of articles published before 1998 were unavailable. The mean age of patients was 50.1±19.0 years (range, 11–79 years) and the female:male ratio was 2.31 (30:13).…”
Section: Resultsmentioning
confidence: 99%
“…Diagnosis relies on clinical and histopathological correlation. On histopathological examination, the lack of hyperplastic thyroid tissue often suggests a hyperfunctioning thyroid cancer (28).…”
Section: Discussionmentioning
confidence: 99%
“…Autonomic thyroid carcinomas are very rare, although published literature showed an increase of these cases in adults [ [2] , [3] , [4] , 6 , 9 ]. Until 2008, 14 relevant case series described 1124 cases of solitary hyperfunctioning nodules submitted to surgery and associated with thyroid cancer, but only in 35 the cancer was in the hyperfunctioning nodule [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Luca Giovanella et al reported a 68-year-old female with a solid/trabecullar follicular carcinoma inside a 5 cm hot nodule [ 10 ]. Seven case reports described papillary carcinomas inside autonomously functioning nodules [ 1 , 2 , 4 , 6 , 8 , 9 , 11 ]. Mehmet Uludag et al published a report of a micropapillary thyroid cancer in a Marine-Lenhart Syndrome nodule [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation